2014
DOI: 10.1007/s00432-014-1751-y
|View full text |Cite
|
Sign up to set email alerts
|

Mutations of EGFR or KRAS and expression of chemotherapy-related genes based on small biopsy samples in stage IIIB and IV inoperable non-small cell lung cancer

Abstract: Mutations and expression of chemotherapy-related genes may provide a basis for the selection of suitable molecular markers for individual treatment in a population with stage IIIB and IV NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…The relationship between EGFR mutation and peripheral structure invasion can provide a basis for comprehensive therapy. Indeed, postoperative patients with EGFR mutation show higher efficacy rates to targeted therapy and chemotherapy compared with wild-type patients [21]. Patients harboring EGFR mutation are prone to recurrence in the incision margin [2224], and have a high metastasis rate [25]; however, they still show higher survival after recurrence [2628].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between EGFR mutation and peripheral structure invasion can provide a basis for comprehensive therapy. Indeed, postoperative patients with EGFR mutation show higher efficacy rates to targeted therapy and chemotherapy compared with wild-type patients [21]. Patients harboring EGFR mutation are prone to recurrence in the incision margin [2224], and have a high metastasis rate [25]; however, they still show higher survival after recurrence [2628].…”
Section: Discussionmentioning
confidence: 99%
“…Patients harboring EGFR mutation are prone to recurrence in the incision margin [2224], and have a high metastasis rate [25]; however, they still show higher survival after recurrence [2628]. For instance, the 5-year survival rate in patients with EGFR mutation was shown to be higher than that of cases without mutation [21], which may be related to drug sensitivity and comprehensive treatment. Therefore, clarifying the clinical characteristics of early lung adenocarcinoma patients with EGFR mutation aims to provide a basis for clinical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been proven that the pathological immunohistochemistry and expression of biological markers between biopsy samples and surgical samples are well correlated (7 ,1315 ). In the past 10 years, multi-gene detection analysis has been done using biopsy samples, which provide important gene phenotyping decision-making evidence for the use of treatment drugs such as molecular-targeted drugs (1417). The success rate of PDTX modeling using surgical samples has been reported to be 25–40% (11,18,19).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, poorly differentiated tumors may also be correlated with chemoresistance in NSCLC . A recent study revealed that the expression of excision repair cross‐complementing group 1 (ERCC1), which repairs platinum‐induced DNA damage in patients with poorly differentiated adenocarcinoma, was significantly higher than that found in patients with well‐moderately differentiated non‐adenocarcinomas . This finding suggests that high levels of ERCC1 expression in poorly differentiated tumors may be predictive of a poor response to platinum‐based chemotherapy in NSCLC.…”
Section: Discussionmentioning
confidence: 99%